Accelerating safe small modular reactor development in Southeast Asia. (February 2022) - Nian, Victor; Ghori, Amjad; Guerra, Eddie M.; Locatelli, Giorgio; Murphy, Paul
Abstract: The emerging economies in Southeast Asia are facing challenges in achieving decarbonisation and energy resilience. Small modular reactors (SMRs) could represent a strategic option but are yet to be properly understood and communicated at the policy level, especially in terms of the favourable implications for energy security and economic and technical benefits, as well as inherent risks and mitigation strategies. With the flourishing designs and start-up companies driving potentially new business models for future nuclear power projects, we present a series of actionable recommendations for utilities and policymakers in Southeast Asia, together with an analysis on the importance of including SMRs as an option in the future energy mix. Highlights: SMRs should be deployed in a vendor-neutral and application focused approach. ASEAN should quickly expand domestic competence and become "knowledgeable customer". Build regional/global collaboration and develop stakeholder engagement strategies. Engage independent advisory panel in technology and project assessment/landing. Develop business models to demonstrate commercial viability in the ASEAN context.